PEMBERDAYAAN MASYARAKAT PESISIR MELALUI BUDIDAYA RUMPUT LAUT DAN PENGOLAHAN HASIL TAMBAK DI DESA PULOKERTO KECAMATAN KRATON - Miftahul Huda (LPPM Universitas Yudharta Pasuruan, 2018)
Real Work Lecture is a student learning process through various activities directly in the midst of the community and students strive to be part of the community, and actively and creatively involved in the dynamics that occur in the community. Students have a strategic role as agents of change. Real Work Lecture (KKN-T Kemaritiman) is one form of student service to the community through the provision of empowerment assistance, training, counseling, mentoring, mentoring, and to awaken the potential that is owned and help improve the quality of life of the community. Students will get generative abilities in the form of life skills. Observations were made with the question and answer method, documentation, and looking directly at the field. Based on the results of the observation, the KKN-T maritime group work program will be determined which includes physical group programs and non-physical group programs. The physical group program is the making of road determinants, while the non-physical group program includes the larudang program socialization, seaweed flour cooking competition, teaching in kindergarten, elementary school, madrasah diniyah, TPQ, computer lessons, Indonesian Anniversary competition participation, sea picking, counseling and examination health, mentoring of posyandu, fatayat, dibaan, sholawatan, tahlilan, and closing of maritime KKN-T. Judging from the above programs perperan students as facilitators, and motivators. The maritime KKN-T implementation began on August 1-31 2018 Pulokerto village was relatively smooth. Thus, after the KKN-T Kemaritiman activity ends, it is expected that the residents of Pulokerto village can continue to develop all the potential that exists in their village.